Labour Relations in Canada in Light of Provincial Cleavages for Migrant Farm Workers - Moldovan, Alexander (Glendon Journal of International Studies, 2015)
Despite the Seasonal Agricultural Worker and Temporary Foreign Worker programs existing under federal legal jurisdiction, provincial authority with respects to health, housing and labour codes encroaches upon many issues that are relevant to the lives of migrant workers. The asymmetrical standardization of various jurisdictions exacerbates a huge cleavage in the Canadian human rights regime in relation to migrant workers. Using an array of reports—that vary in their respective source bases from labour unions to academic and government publications—this paper examines inter-provincial differences in the aforementioned areas of issues to demonstrate that the federal/provincial division of powers acts as an impediment for the development of rights for temporary migrant workers under the Seasonal Agricultural Worker Program and Temporary Foreign Worker Program. To advance this argument, this paper also illustrates how various provincial governments have interacted with the Governments of Canada and Mexico to limit access to healthcare, housing and collective bargaining. It then promotes the notion that, in the absence of federal uniformity, the dispersed jurisdiction in these areas of issues allows the provinces leverage to experiment with different labour relations regimes; it asserts that although provinces are given room to differ from one another, some of them have attempted to systematically restrict the rights of migrants to housing, healthcare, training, and collective representation. Malgré les programmes pour les «travailleurs étrangers temporaires et les travailleurs agricoles saisonniers » qui existent sous la compétence fédérale, les autorités provinciales ayant trait à la santé, le logement, et les codes du travail empiètent sur plusieurs questions pertinentes à la vie des travailleurs migrants. La standardisation asymétrique d’un grand nombre de juridictions aggrave la grande scission dans le régime canadien des droits de l’homme vis-à-vis des travailleurs migrants. En consultant une grande variété de rédactions provenant de sources diverses telles que des syndicats et des publications académiques et gouvernementales, cet essai examine les différences interprovinciales afin de démontrer que la division de pouvoir entre le niveau fédéral et provincial agit comme obstacle pour les travailleurs migrants sous le programme. Pour avancer cet argument, cet essai illustre comment les gouvernements provinciaux ont collaboré avec les gouvernements du Canada et du Mexique pour limiter l’accès aux médicaments, au logement et à la négociation collective. On promeut ensuite la notion que l’absence d’uniformité fédérale et la dispersion de juridiction permet aux provinces d’expérimenter avec différents régimes de relations de travail; bien que les provinces aient la chance de varier leurs normes, plusieurs d’entre elles ont tenté de limiter systématiquement les droits des travailleurs migrants au logement, aux médicaments, à l’entraînement et à la négociation collective.